Adsorptive and Catalytic Cathodic Stripping Voltammetric Determination of Timonacic - Amin,O.A.R. (2011)
Two sensitive voltammetric techniques (adsorptive and catalytic cathodic stripping) are described for the determination of timonacic, in the presence of copper or nickel ions, respectively. The measured peaks which correspond to the reduction or copper (I) or nickel - timonacic complexes are measured at -773 and -782 mV, respectively. The different experimental parameters have been carefully studied. The methods have been fully validated. The detection limits were 1.5 and 13.6 ng mL-1, respectively. The methods have been applied for the determination of timonacic in pharmaceutical tablets. The obtained results have been compared statistically with those obtained from a published method.